A RARE CASE OF MICROPROLACTINOMA AND GRANULOMATOUS MASTITIS - Teh, Kai Xuan; Tee, Hwee Ching; Ho, Jin Hui; Tham, Joon Hi; Pan, Ann Feng (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Idiopathic granulomatous mastitis (IGM) is a benign and rare chronic inflammatory disease of the breast. However, its clinical presentation can mimic a breast malignancy or abscess. The aetiology is often unknown but several predisposing factors were identified, including patients with autoimmune disorders, hyperprolactinemia secondary to pregnancy, lactation, dopamine antagonist usage or pituitary adenoma. CASE We report a rare case of IGM in a patient with hyperprolactinemia secondary to microprolactinoma. A 45-year-old, para 2, premenopausal female presented to a surgical clinic with a 2 year history of intermittent bilateral galactorrhoea and right breast swelling with pus discharge. There was no menstrual irregularity. Ultrasound of the right breast demonstrated multiloculated hypoechoic collections with internal echogenicities. She was treated with antibiotics; however, there was no clinicalimprovement, and she underwent biopsy of the lesion which revealed chronic granulomatous inflammation, confirming the diagnosis of IGM. She was also found to have hyperprolactinemia at 125.9 ng/ml secondary to a microprolactinoma and was started on cabergoline. Two weeks post treatment, the prolactin level normalized with resolution of galactorrhoea. CONCLUSION Hyperprolactinemia is one of the predisposing factors for the development of IGM by increasing inflammation of the breast tissue. When evaluating for IGM, serum prolactin should always be measured to exclude elevated prolactin levels. The cause of hyperprolactinemia should be further investigated and addressed, and treatment with dopamine receptor agonist could reduce recurrence of IGM.